2012
DOI: 10.1038/nrurol.2012.57
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative chemotherapy for upper tract urothelial cancer

Abstract: Upper tract urothelial cancer (UTUC) is an aggressive disease associated with significant morbidity and mortality. Radical nephroureterectomy (RNU) with bladder cuff removal is considered the standard of care for most invasive UTUCs but distant relapses after surgery for locally advanced, high-grade disease are common. Although multimodality treatment with perioperative chemotherapy has been investigated thoroughly in recent years, adjuvant chemotherapy has primarily been analyzed in small retrospective uncont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 97 publications
(50 reference statements)
0
14
0
Order By: Relevance
“…Little progress is noted in treating advanced UC compared with other types of malignancies, even with chemotherapy, 25,26 although some small series showed a promising sensitivity to everolimus in bladder cancer with tuberous sclerosis complex 1 mutation. 27 Recent genomic studies demonstrated that diverse genomic aberrations existed in bladder UC, 28,29 and that bladder cancers split into three pan-cancer subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Little progress is noted in treating advanced UC compared with other types of malignancies, even with chemotherapy, 25,26 although some small series showed a promising sensitivity to everolimus in bladder cancer with tuberous sclerosis complex 1 mutation. 27 Recent genomic studies demonstrated that diverse genomic aberrations existed in bladder UC, 28,29 and that bladder cancers split into three pan-cancer subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…There is a solid clinical rationale to utilize neoadjuvant rather than adjuvant chemotherapy for appropriately selected patients with UTUC, as the decline in renal function after nephrectomy may hinder effective chemotherapy dosing in an adjuvant setting (12)(13)(14). Moreover, a significant number of UTUC patients may already have a degree of renal insufficiency at the time of diagnosis (13,14).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a significant number of UTUC patients may already have a degree of renal insufficiency at the time of diagnosis (13,14). Recent reports have shown rates of up to 14% and 53% for complete response and down staging, after utilization of neoadjuvant chemotherapy in patients with locally advanced UTUC (12,15).…”
Section: Discussionmentioning
confidence: 99%
“…When administering chemotherapy for urothelial carcinoma, cisplatin-containing regimens are superior to carboplatin-based therapy with respect to patient survival outcomes [30]. In patients with metastatic urothelial cancer, multiple studies have shown that carboplatin-based regimens are less toxic compared with cisplatin-based therapy [31].…”
Section: Preserved Preoperative Renal Functionmentioning
confidence: 99%
“…Unlike bladder cancer, where more accurate staging can be achieved with adequate transurethral resection, our current staging modalities for UTUC are less consistent in their ability to accurately identify invasive carcinoma. This raises the possibility of overtreatment in some patients without pathologically proven muscle invasive disease [30,45,46]. In a large retrospective multi-institutional review, Hellenthal et al found that only 39% of UTUC patients who underwent RNU actually had high-risk features ( ‡pT3 or ‡pN1) on final pathology, thus potentially risking overtreatment in 61% of patients [47].…”
Section: Pathologic Downstaging Prior To Surgerymentioning
confidence: 99%